Immunity Against Tetanus Infection, Risk Factors for Non-Protection, and Validation of a Rapid Immunotest Kit among Hospitalized Children in Nigeria - Orimadegun, Adebola E.; Orimadegun, Bose E.; Adepoju, Akinlolu A. (Frontiers in Neurology, 2013)
Seroepidemiological studies of tetanus in Africans have focused mainly on adults especially pregnant women and data on children are scarcely reported. We investigated the seroprevalence of protective immunity level, determined risk factors for non-protection against tetanus and evaluated the performance of Tetanos Quick Stick® (TQS) among hospitalised children aged 1 to 9 years in Nigeria. Blood IgG antibody levels to tetanus was determined using enzyme-linked immunosorbent assay (ELISA) in the laboratory and TQS (an immunochromatogrphic test) at the bedside for 304 children admitted into emergency unit of a tertiary hospital in Ibadan Nigeria. Demographic information and vaccination history were also collected. TQS results were compared with anti-tetanus antibody measured by ELISA using seroprotection cut-off of 0.1 IU/ml. Seroprevalence of protective level of immunity against tetanus using ELISA and TQS methods was 44.7% and 45.4% respectively. Protective level of immunity increased as age increases. Of the seven potential factors assessed, male gender and being second or more position among mother’s children were independent predictors of non-protective level of immunity. Absence of history of recent tetanus toxoid injection was significantly associated with non-protective level of immunity in univariate analysis but not logistic regression model. The agreement between the ELISA and the TQS results was good with a k coefficient of 0.931. TQS sensitivity was, 95.7%, specificity 97.6%, positive predictive value 98.0% and negative predictive values 96.0%. This study showed that lack of protective immunity against tetanus is common; few demographic characteristics correctly predict non-protection and IgG antibody levels to tetanus was accurately detected by TQS.